PENGARUH KETERSEDIAAN GREEN PRODUCT TERHADAP KEPUTUSAN PEMBELIAN PRODUK MERCHANDISE DI STARBUCKS FOOD CENTRUM SUNTER JAKARTA UTARA - Stevica Panggih; Antonius Rizki Krisnadi (Lembaga Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Pariwisata Bogor, 2021)
Environmental pollution is caused by the lack of human awareness to protect the environment and plastic waste has the highest percentage of waste. Starbucks as a coffee shop spread across many countries plays a role in reducing plastic waste to support the green product movement. This research was aimed to know about the influence of green product indicators. Green product indicator itself consists of (3) items, which consists of green product, green product performance in accordance with consumer expectations, raw materials are not dangerous. The location that was the subject of research is Starbucks Coffee, a coffee shop located in North Jakarta. The fixed sample was 85 respondents, taken by purposive sampling method, which they must be at least 20-60 years-old, and have bought food or drink in Starbucks Coffee Food Centrum. The test is results in this study indicate that there are two that give partial influence, namely green product performance and raw materials are not dangerous, while green product has no effect. But when conducted simultaneous testing, all indicators of green product expressed influence the purchase decision at Starbucks Coffee Food Centrum significantly. it means all variables (X1-X3) simultaneously influences consumer’s perceived intention in Starbucks Coffee Food Centrum. Both of those statements can be concluded as the reason of buying in Starbucks Coffee Food Centrum, not just because only one reason, but more than one indicators must be strengthened one another when it’s tested simultaneously.